1997
DOI: 10.1093/jac/40.3.449
|View full text |Cite
|
Sign up to set email alerts
|

Teicoplanin in the treatment of enterococcal endocarditis: clinical and microbiological study

Abstract: Seven cases of enterococcal endocarditis treated with teicoplanin (7-10 mg/kg/day for 28-105 days) alone (one case) or in combination with aminoglycosides (six cases) were reviewed. All patients were cured. Serum bactericidal activity titres after intravenous gentamicin (5 mg/kg every 24 h) and teicoplanin (10 mg/kg every 24 h) were measured on day 7 of treatment in four patients against five enterococcal isolates: mean titres were 1:54 (range 1:16-64) and 1:22 (1:8-32) at 0.5 and 24 h post-infusion, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…Teicoplanin plus gentamicin, both administered once a day, could be an alternative therapeutic approach for selected cases of enterococcal endocarditis on an outpatient basis, probably after 2 weeks of treatment in the hospital environment. Our experimental results showed that teicoplanin plus gentamicin, both administered once a day by means of a controlled infusion pump system to mimic human kinetics, was as effective as the elective treatment with ampicillin at 2 g/4 h plus gentamicin at 1 mg/kg/8 h. The results from a recent clinical study by Venditti et al (38) provide evidence that a single daily dose of teicoplanin plus gentamicin could be a good therapeutic option for home treatment of selected cases of enterococcal endocarditis. Six patients with enterococcal endocarditis were cured when treated with teicoplanin in combination with gentamicin or netilmicin administered once a day.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Teicoplanin plus gentamicin, both administered once a day, could be an alternative therapeutic approach for selected cases of enterococcal endocarditis on an outpatient basis, probably after 2 weeks of treatment in the hospital environment. Our experimental results showed that teicoplanin plus gentamicin, both administered once a day by means of a controlled infusion pump system to mimic human kinetics, was as effective as the elective treatment with ampicillin at 2 g/4 h plus gentamicin at 1 mg/kg/8 h. The results from a recent clinical study by Venditti et al (38) provide evidence that a single daily dose of teicoplanin plus gentamicin could be a good therapeutic option for home treatment of selected cases of enterococcal endocarditis. Six patients with enterococcal endocarditis were cured when treated with teicoplanin in combination with gentamicin or netilmicin administered once a day.…”
Section: Discussionmentioning
confidence: 55%
“…Martino et al (27) treated four patients; three of them were cured, and one relapsed and was cured with surgery plus treatment with ampicillin and gentamicin. A 4-week course of 10 mg/kg/day has been found to be effective against native streptococcal endocarditis (38). Presterl et al (33) treated and cured five patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dawka nasycająca pełni zasadniczą rolę, ponieważ lek wią-że się łatwo z białkami krwi (≥ 98%) i powoli penetruje do wegetacji [140]. Jednak tylko w ograniczonej liczbie badań retrospektywnych oceniano skuteczność teikoplaniny w IZW spowodowanym paciorkowcami [141] i enterokokami [142].…”
Section: Grupa Wrażliwych Na Penicylinę Paciorkowców Jamy Ustnej Orazunclassified
“…Grupa szczepów w pełni opornych wciąż się powiększa. W raportach oceniających dużą liczbę próbek częstość wystę-powania szczepów Streptococcus mitis i Streptococcus oralis o względnej i pełnej oporności oceniano na ponad 30% [142,143]. Odwrotnie, ponad 99% paciorkowców pokarmowych pozostaje wrażliwych na penicylinę.…”
Section: Grupa Opornych Na Penicylinę Paciorkowców Jamy Ustnej Oraz Sunclassified
“…Recent large strain collections report .30% of relatively and fully resistant S. mitis and S. oralis. 118,119 Conversely, .99% of group D streptococci remain penicillin susceptible. Treatment guidelines for penicillin-resistant streptococcal IE rely on retrospective series.…”
Section: Penicillin-resistant Oral Streptococci and Group D Streptococcimentioning
confidence: 99%